Improvement of stress LVEF rather than rest LVEF after coronary revascularisation in patients with ischaemic cardiomyopathy and viable myocardium. Issue 3 (14th February 2005) - Rizzello, V; Poldermans, D; Biagini, E; Schinkel, A F L; van Domburg, R; Elhendy, A; Vourvouri, E C; Bountioukos, M; Lombardo, A; Krenning, B; Roelandt, J R T C; Bax, J J
Abstract : Objective: To evaluate prospectively the response of left ventricular ejection fraction (LVEF) to high dose dobutamine infusion in patients showing substantial viability, with and without improved resting LVEF after revascularisation. Methods: Before and 9–12 months after revascularisation, 50 patients with ischaemic cardiomyopathy (LVEF 32 (8)%) and substantial myocardial viability (⩾ 4 viable segments) underwent radionuclide ventriculography and dobutamine stress echocardiography. Patients were divided into group 1, patients with, and group 2, patients without significant improvement in resting LVEF (⩾ 5% by radionuclide ventriculography) after revascularisation. The response of LVEF during dobutamine stress echocardiography was compared in these two groups. Results: Groups 1 and 2 were comparable in baseline characteristics, resting LVEF, and number of viable segments (mean (SD) 7 (4) v 6 (2), not significant). After revascularisation, the LVEF response during dobutamine stress echocardiography improved significantly in both groups (group 1, 34 (10)% to 56 (8)%; group 2, 32 (10)% to 46 (11)%; both p < 0.001). Interestingly, although resting LVEF did not improve in group 2, peak stress LVEF after revascularisation did (p < 0.001). Group 1 patients had, however, a greater increase in peak stress LVEF (group 1, 22 (10)%; group 2, 13 (9)%; p < 0.01). New York Heart Association and Canadian Cardiovascular Society classes decreased in both groups. Conclusions: Although patients with viable myocardium did not always have improved rest LVEF after revascularisation, peak stress LVEF improved. Assessment of improvement of resting function may not be the ideal end point to evaluate successful revascularisation.